Regulation of Synthesis and Roles of Hyaluronan in Peritoneal Dialysis. (13th October 2015) - Bowen, Timothy; Meran, Soma; Williams, Aled P.; Newbury, Lucy J.; Sauter, Matthias; Sitter, Thomas
Abstract : Hyaluronan (HA) is a ubiquitous extracellular matrix glycosaminoglycan composed of repeated disaccharide units of alternating D-glucuronic acid and D-N-acetylglucosamine residues linked via alternating β -1, 4 and β -1, 3 glycosidic bonds. HA is synthesized in humans by HA synthase (HAS) enzymes 1, 2, and 3, which are encoded by the corresponding HAS genes. Previous in vitro studies have shown characteristic changes in HAS expression and increased HA synthesis in response to wounding and proinflammatory cytokines in human peritoneal mesothelial cells. In addition, in vivo models and human peritoneal biopsy samples have provided evidence of changes in HA metabolism in the fibrosis that at present accompanies peritoneal dialysis treatment. This review discusses these published observations and how they might contribute to improvement in peritoneal dialysis.